Paisagismo com nativas: o mercado de oferta e demanda de espécies ornamentais na região metropolitana de Sorocaba - Marum, Suéllen Sandi Sojo (Universidade Federal de São Carlos, 2022)
Landscaping is essential for ecological balance, as green spaces are being increasingly occupied with urbanization. It is incongruous that in a country with one of the richest, most diverse and important floras in the world, most of the plants used in landscaping are still exotic, some of which are invasive. With the little appreciation of native species, the urgency of modifying this dynamic is understandable, and analyzing the high rate of urbanization in a global context, the water crisis and the threat of extinction of so many species of fauna and flora, it appears that the Cities must now be seen as ecological entities, where human action must try to reestablish the local environmental balance. Since the State of São Paulo is the most urbanized place in Brazil, concentrating the largest contingent of population residing in urban areas, in addition to the presence of two threatened biomes, Atlantic Forest and Cerrado, we limit one of its most economically significant Metropolitan Regions as an object of study, the Metropolitan Region of Sorocaba (RMS), in order to carry out a survey of local landscape demand and which are the main species offered in regional commerce in the scale of production, sale and management, identifying the groups with the highest output and if there is a market for herbs, shrubs and local native trees for ornamentation, and what material is currently available to promote this sector. The methodology focused on bibliographic research to understand the importance of biodiversity in urban gardens, and quantitative and qualitative research in the floristic market of this regional cut, as well as data collection of working professionals and population profile on the subject, with the purpose of understanding if there is a demand for these vegetations and how their supply and availability in nurseries and floras works. Thus, the standardization of landscapes in the region was verified, where the most offered plants are exotic and little diverse, and the professionals responsible for the projects have an aesthetic vision in disagreement with the population sample studied.

L'aménagement paysager est essentiel pour l'équilibre écologique, car les espaces verts sont de plus en plus occupé par l'urbanisation. Il est incongru que dans un pays avec l'un des plus riche, diversifié et important dans le monde, encore la plupart des plantes utilisées dans l'aménagement paysager exotiques, dont certaines sont envahissantes. Avec peu d'appréciation des espèces indigènes, comprendre l'urgence de changer cette dynamique, et analyser le taux élevé d'urbanisation dans un contexte mondial, la crise de l'eau et la menace d'extinction de tant d'espèces de faune et de flore, il apparaît que les villes doivent désormais être vues comme des entités écologiques, où l'action l'activité anthropique doit tenter de rétablir l'équilibre environnemental local. Étant donné que l'État de São Paulo est le l'endroit le plus urbanisé du Brésil, concentrant le plus grand contingent de population résidant dans zones urbaines, en plus de la présence de deux biomes menacés, la forêt atlantique et le Cerrado, nous limitons une de ses régions métropolitaines les plus importantes sur le plan économique comme objet d'étude, Région métropolitaine de Sorocaba (RMS), afin de réaliser une enquête sur la demande paysage local et quelles sont les principales espèces proposées dans le commerce régional à l'échelle la production, la vente et la gestion, en identifiant les groupes les plus performants et s'il existe un marché pour herbacées, arbustes et arbres indigènes pour l'ornementation, et quel matériau est actuellement disponibles pour promouvoir ce secteur. La méthodologie axée sur la recherche la littérature pour comprendre l'importance de la biodiversité dans les jardins urbains, et enquête quantitative et qualitative sur le marché floristique de cette coupe régionale, ainsi que collecte de données sur les professionnels en activité et le profil de la population sur le sujet, dans le but de afin de comprendre s'il existe une demande pour ces végétations et comment l'offre et leur disponibilité dans les pépinières et la flore. Ainsi, la standardisation de paysages de la région, où les plantes les plus proposées sont exotiques et peu diversifiées, et les les professionnels responsables des projets ont une vision esthétique en désaccord avec l'échantillon population étudiée.

Die Landschaftsgestaltung ist für das ökologische Gleichgewicht ebenso wichtig wie Grünflächen zunehmend mit Urbanisierung beschäftigt. Es ist unpassend, dass in einem Land mit einem der meisten Reich, vielfältig und wichtig in der Welt, werden immer noch die meisten Pflanzen in der Landschaftsgestaltung verwendet exotisch, von denen einige invasiv sind. Mit wenig Wertschätzung für einheimische Arten, die Dringlichkeit zu verstehen, diese Dynamik zu ändern, und die hohe Urbanisierungsrate zu analysieren im globalen Kontext die Wasserkrise und das drohende Aussterben so vieler Tier- und Pflanzenarten, Es scheint, dass Städte jetzt als ökologische Einheiten betrachtet werden müssen, in denen Maßnahmen ergriffen werden müssen anthropische Aktivitäten müssen versuchen, das lokale ökologische Gleichgewicht wiederherzustellen. Da ist der Bundesstaat São Paulo der am stärksten urbanisierte Ort in Brasilien, in dem sich die größte Bevölkerungsgruppe konzentriert städtische Gebiete, zusätzlich zum Vorhandensein von zwei bedrohten Biomen, dem Atlantischen Regenwald und dem Cerrado, begrenzen wir a seiner wirtschaftlich bedeutendsten Metropolregionen als Untersuchungsgegenstand, der Metropolregion Sorocaba (RMS), um eine Bedarfserhebung durchzuführen lokale Landschaft und was sind die wichtigsten Arten, die im regionalen Handel im Maßstab von angeboten werden Produktion, Verkauf und Verwaltung, Identifizierung der Gruppen mit der höchsten Leistung und ob es einen Markt dafür gibt Kräuter, Sträucher und einheimische Bäume für die Verzierung und aus welchem ​​Material derzeit verfügbar, um diesen Sektor zu fördern. Die Methodik konzentrierte sich auf die Forschung Literatur, um die Bedeutung der Biodiversität in städtischen Gärten zu verstehen, und quantitative und qualitative Untersuchung im Floristikmarkt dieses regionalen Schnittes, sowie Datenerhebung der Berufstätigen und des Profils der Bevölkerung zum Thema, mit dem Ziel Zweck zu verstehen, ob es eine Nachfrage nach diesen Vegetationen gibt und wie das Angebot und ihre Verfügbarkeit in Baumschulen und Flora. Also die Standardisierung von Landschaften in der Region, wo die meisten angebotenen Pflanzen exotisch und wenig vielfältig sind, und die Fachleute, die für die Projekte verantwortlich sind, haben eine ästhetische Vision, die nicht mit der Probe übereinstimmt Bevölkerung studiert.

El paisajismo es esencial para el equilibrio ecológico, ya que los espacios verdes están siendo cada vez más ocupado con la urbanización. Es incongruente que en un país con uno de los más rico, diverso e importante en el mundo, siendo la mayoría de las plantas utilizadas en el paisajismo exóticos, algunos de los cuales son invasivos. Con poca apreciación de las especies nativas, comprender la urgencia de cambiar esta dinámica, y analizar el alto índice de urbanización en un contexto global, la crisis del agua y la amenaza de extinción de tantas especies de fauna y flora, parece que las ciudades ahora deben ser vistas como entidades ecológicas, donde la acción la actividad antrópica debe tratar de restablecer el equilibrio ambiental local. Dado que el Estado de São Paulo es el lugar más urbanizado de Brasil, concentrando el mayor contingente de población residente en áreas urbanas, además de la presencia de dos biomas amenazados, la Mata Atlántica y el Cerrado, limitamos una de sus regiones metropolitanas económicamente más significativas como objeto de estudio, la Región Metropolitana de Sorocaba (RMS), con el fin de realizar un relevamiento de demanda paisaje local y cuáles son las principales especies que se ofrecen en el comercio regional a escala de producción, venta y gestión, identificando los grupos de mayor producción y si existe mercado para herbáceos, arbustos y árboles nativos para ornamentación, y de qué material se disponible actualmente para promover este sector. La metodología se centró en la investigación. literatura para comprender la importancia de la biodiversidad en los jardines urbanos, y investigación cuantitativa y cualitativa en el mercado florístico de este corte regional, así como recopilación de datos de los profesionales en activo y el perfil de la población sobre el tema, con el objetivo de con el propósito de entender si hay demanda de estas vegetaciones y cómo la oferta y su disponibilidad en viveros y flora. Así, la estandarización de paisajes de la región, donde las plantas más ofertadas son exóticas y poco diversas, y la los profesionales responsables de los proyectos tienen una visión estética en desacuerdo con la muestra población estudiada.

景观美化对于生态平衡至关重要，因为绿色空间正在 越来越忙于城市化。在一个拥有最多 世界上丰富、多样和重要的植物，仍然是园林绿化中使用的大部分植物 异国情调，其中一些是侵入性的。对本土物种的欣赏很少， 了解改变这种动态的紧迫性，并分析高城市化率 在全球范围内，水资源危机和许多动植物物种灭绝的威胁， 看来，现在必须将城市视为生态实体，采取行动 人类活动必须努力重建当地的环境平衡。由于圣保罗州是 巴西城市化程度最高的地方，集中了居住在 城市地区，除了存在两个受威胁的生物群系，大西洋森林和塞拉多，我们限制了 将其最具经济意义的大都市地区作为研究对象， 索罗卡巴大都会区 (RMS)，以开展需求调查 当地景观以及在区域贸易中提供的主要物种是什么 生产、销售和管理，确定产量最高的群体以及是否有市场 用于装饰的草本植物、灌木和原生树木，以及什么材料是 目前可用于推广该部门。该方法侧重于研究 了解生物多样性在城市花园中的重要性的文献，以及 对该区域切块的植物市场进行定量和定性调查，以及 收集工作专业人员的数据和有关该主题的人口概况，目的是 目的是了解这些植被是否有需求，以及供应和 它们在苗圃和植物群中的可用性。因此，标准化 该地区的景观，提供最多的植物是异国情调且不是很多样化，以及 负责项目的专业人员对样本有审美眼光 研究的人群。

景觀美化對於生態平衡至關重要，因為綠色空間正在 越來越忙於城市化。在一個擁有最多 世界上豐富、多樣和重要的植物，仍然是園林綠化中使用的大部分植物 異國情調，其中一些是侵入性的。對本土物種的欣賞很少， 了解改變這種動態的緊迫性，並分析高城市化率 在全球範圍內，水資源危機和許多動植物物種滅絕的威脅， 看來，現在必須將城市視為生態實體，採取行動 人類活動必須努力重建當地的環境平衡。由於聖保羅州是 巴西城市化程度最高的地方，集中了居住在 城市地區，除了存在兩個受威脅的生物群系，大西洋森林和塞拉多，我們限制了 將其最具經濟意義的大都市地區作為研究對象， 索羅卡巴大都會區 (RMS)，以開展需求調查 當地景觀以及在區域貿易中提供的主要物種是什麼 生產、銷售和管理，確定產量最高的群體以及是否有市場 用於裝飾的草本植物、灌木和原生樹木，以及什麼材料是 目前可用於推廣該部門。該方法側重於研究 了解生物多樣性在城市花園中的重要性的文獻，以及 對該區域切塊的植物市場進行定量和定性調查，以及 收集工作專業人員的數據和有關該主題的人口概況，目的是 目的是了解這些植被是否有需求，以及供應和 它們在苗圃和植物群中的可用性。因此，標準化 該地區的景觀，提供最多的植物是異國情調且不是很多樣化，以及 負責項目的專業人員對樣本有審美眼光 研究的人群。

緑地が開発されているため、造園は生態系のバランスに不可欠です。 都市化でますます忙しい。最も人口の多い国の 1 つで、 豊かで、多様で、世界で重要であり、造園に使用される植物のほとんど エキゾチックで、そのうちのいくつかは侵略的です。在来種をほとんど評価せずに、 このダイナミクスを変える緊急性を理解し、都市化率の高さを分析する 地球規模の状況では、水の危機と非常に多くの種の動植物の絶滅の脅威、 都市は今や生態学的な実体として見られなければならないようです。 人間活動は、地域の環境バランスを再確立しようとしなければなりません。サンパウロ州なので、 ブラジルで最も都市化された場所で、居住する人口の最大の派遣団が集中しています 都市部では、大西洋岸森林とセラードという 2 つの絶滅危惧種の生物群系が存在することに加えて、 研究対象として最も経済的に重要な大都市圏の 需要調査を行うため、ソロカバ大都市圏（RMS） 地域の景観と、地域の商業で提供される主な種は何ですか 生産、販売、管理、生産量が最も多いグループを特定し、市場があるかどうかを確認します。 装飾用のハーブ、低木、在来の木、およびその素材は何か このセクターを促進するために現在利用可能です。研究に焦点を当てた方法論 都市庭園における生物多様性の重要性を理解するための文献、および この地域カットの植物市場における定量的および定性的な調査、および 働く専門家のデータ収集と、この主題に関する人口のプロファイル。 これらの植生に需要があるかどうか、および供給と供給がどのように行われているかを理解する目的 苗床と植物相でのそれらの入手可能性。したがって、の標準化 最も提供される植物がエキゾチックであまり多様ではない地域の風景、および プロジェクトを担当する専門家は、サンプルと一致しない審美的なビジョンを持っています 人口が調査されました。
Landscaping with natives: the supply and demand market for ornamental species in the metropolitan region of Sorocaba
Landschaftsgestaltung mit Einheimischen: Der Angebots- und Nachfragemarkt für Zierarten in der Metropolregion Sorocaba
Keywords: Plantas; Paisagismo; Ecológico; Ecogênese; Paisagismo funcional; Biodiversidade; végétaux; aménagement; Écologique; échogenèse; Aménagement paysager fonctionnel; biodiversité; Pflanzen; Landschaftsbau; Ökologisch; Echogenese; Funktionale landschaftsgestaltung; Biodiversität; Plants; Landscaping; Ecological; Echogenesis; Functional landscaping; Biodiversity; Paisajismo; Plantas; Ecogénesis; Ecológico; Paisajismo funcional; Biodiversidad; 植物; 造園; 生態学的; エコージェネシス; 機能美化; 生物多様性; 植物; 生物多樣性; 功能美化; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PAISAGISMO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA